Serological testing for syphilis in the differential diagnosis of cognitive decline and polyneuropathy in geriatric patients - Marija Djukic; Helmut Eiffert; Peter Lange; Ioanna Giotaki; Jana Seele; Roland Nau (BMC Geriatrics, 2023)
Abstract Background In the 19th century, neurosyphilis was the most frequent cause of dementia in Western Europe. Now dementia caused by syphilis has become rare in Germany. We studied whether routine testing of patients with cognitive abnormalities or neuropathy for antibodies against Treponema pallidum has therapeutic consequences in geriatric patients. Methods A Treponema pallidum electrochemiluminescence immunoassay (TP-ECLIA) is routinely performed in all in-patients treated at our institution with cognitve decline or neuropathy and no or insufficient previous diagnostic workup. Patients with a positive TP-ECLIA treated from October 2015 to January 2022 (76 months) were retrospectively evaluated. In cases of positive TP-ECLIA, further specific laboratory investigations were performed to assess whether antibiotic therapy was indicated. Results In 42 of 4116 patients (1.0%), TP-ECLIA detected antibodies directed against Treponema in serum. Specifity of these antibodies was ensured by immunoblot in 22 patients (11 × positiv, 11 × borderline values). Treponema-specific IgM was detectable in the serum of one patient, in 3 patients the Rapid Plasma Reagin (RPR) test, a modified Venereal Disease Research Laboratory test (VDRL), in serum was positiv. CSF analysis was performed in 10 patients. One patient had CSF pleocytosis. In 2 other patients, the Treponema-specific IgG antibody index was elevated. 5 patients received antibiotic therapy (4 × ceftriaxone 2 g/d i.v., 1 × doxycycline 300 mg/d p.o.). Conclusion In approx. 1‰ of patients with previously undiagnosed or not sufficiently diagnosed cognitive decline or neuropathy, the diagnostic workup for active syphilis resulted in a course of antibiotic treatment.